2018
DOI: 10.1111/obr.12756
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity as major, modifiable risk factors for urinary incontinence in young to mid‐aged women: a systematic review and meta‐analysis

Abstract: The purpose of this review and meta-analysis was to evaluate overweight and obesity as risk factors for urinary incontinence in young to mid-aged women. Understanding these relationships during this life stage is important as early onset increases the risk for developing severe and persistent incontinence. A systematic search resulted in 497 citations, 14 of which were retained for review. Data were analysed by overweight and obesity and by subtype of urinary incontinence - stress, urge, mixed and severe. When… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 37 publications
5
28
0
2
Order By: Relevance
“…The prevalence of UI was lower in young women with tertiary education, and significantly higher in women with BMI > 30, parous women, women with high psychological distress, and current smokers. These findings are consistent with previous research on the correlates of UI 13‐16 …”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of UI was lower in young women with tertiary education, and significantly higher in women with BMI > 30, parous women, women with high psychological distress, and current smokers. These findings are consistent with previous research on the correlates of UI 13‐16 …”
Section: Discussionsupporting
confidence: 93%
“…diabetes and asthma [11], depressive symptoms [12], gestational diabetes [13], back pain [14] and urinary incontinence. [15]).…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies are cross sectional and may be limited by selection bias, so it is difficult to conclude whether women do not leak because they exercise or whether they can exercise because they do not leak. It may also be that the relationship between low-impact activities and decreased risk of UI is mediated by prevention of weight gain, given that overweight and obesity are strong predictors of UI [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy, vaginal delivery, high body mass index (BMI) and being middle-aged (≥ 40 years) are known risk factors for the development of UI [ 2 , 5 , 6 ]. However, studies have also shown that nulliparous young women experience UI, especially women participating in high-impact activities and sports [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%